An Overview of Mites on Grapevine and the Discovery of a new Phytoseiidae Species; Typhlodromus (Typhlodromus) spiceae - Vermaak, M.; Ueckermann, E.A.; Veldtman, R.; Addison, P. (South African Journal of Enology and Viticulture, 2021)
The common grapevine (Vitis vinifera L.) is the main species used for wine making, with South Africa being one of the top wine exporting countries. Grapevine is vulnerable to a range of pests, including mites. We present an overview of phytophagous and predatory mites on grapevine in South Africa and describe a new phytoseiid species which was discovered in the winelands region of Wellington, South Africa. Grapevine shoots with leaves were collected over two growing seasons at four farms in Wellington. A nursery, mother block and a commercial vineyard were selected on each farm. The mites were removed with a mite brushing machine and slide mounted. The Phytoseiidae Database, as well the most recent relevant literature were used in confirming the new species. Illustrations of the new species were made using photographs taken by Zeiss Axioskop TM Research that included a Zen Soft Imaging System. The new Typhlodromus species, Typhlodromus (Typhlodromus) spiceae sp.n., is set apart from closely related species by setae Z4 being 0.7 times the length of Z5 and by having a short, saccular and thick-walled spermathecal. This species was found together with one phytophagous mite species (Brevipalpus lewisi) and several predatory mite species (Typhlodromus praeacutus, Typhlodromus saevus, Eusieus addoensis). A key to identify females of the South African species of Typhlodromus (Typhlodromus) is provided.